A survey of adult and pediatric urologists on current practice in antibiotic prophylaxis for ureteral stent removal. Issue 1 (February 2021) - Berrondo, Claudia; Ahn, Jennifer J.; Merguerian, Paul A.; Lendvay, Thomas S.; Shnorhavorian, Margarett
Summary: Introduction: Recommendations for antibiotic prophylaxis prior to cystourethroscopy with manipulation are based on limited evidence and may not be applicable to procedures without tissue resection such as ureteral stent removal. Objectives: Our objectives were to investigate and compare practice patterns among adult and pediatric urologists on antibiotic prophylaxis for stent removal. Study design: An online survey was distributed to members of the Endourological Society (EUS) and Societies for Pediatric Urology (SPU) including questions about provider demographics and practice patterns. Adult urologists were defined as EUS member respondents and pediatric urologists were defined as SPU member respondents. Comparisons were made using Pearson's Chi-Square analysis. Results: Of 2544 adult urologists surveyed, 258 (10%) completed the survey and of 714 pediatric urologists surveyed, 180 (25%) completed the survey (Table 1). Pediatric urologists report using antibiotic prophylaxis "most of the time" (i.e. ≥ 75% of the time) more often than adult urologist when removing stents by string or operating room cystoscopy but less often when removing stents by office cystoscopy. Pediatric urologists report using antibiotic prophylaxis "most of the time" more often than adult urologists after pyeloplasty, ureteroscopy and ureteral reimplantation. There is no difference in reported duration of prophylaxis between adult and pediatric urologists, with 64% giving a single dose. Pediatric urologists report obtaining a urine culture (UC) "most of the time" more often than adult urologists (32% vs 15%, p < 0.001), but there is no difference in reported use of antibiotic treatment by UC result. Sixty-four percent of survey respondents report giving patients with negative UC antibiotic treatment, and 93% of survey respondents report treating patients with asymptomatic bacteriuria (defined as patients with a positive urine culture but no symptoms) with antibiotics. Discussion: There is variation in reported practice among surveyed adult and pediatric urologists regarding antibiotic prophylaxis prior to stent removal. Overall, pediatric urologists report using antibiotic prophylaxis prior to stent removal more often than adult urologists. Conclusions: This variation in practice combined with lack of evidence to support the use of antibiotic prophylaxis prior to ureteral stent removal underscores the need for additional research to guide the development of evidence-driven guidelines for both adult and pediatric patients. Summary Figure Proportion of adult and pediatric urologists reporting prescribing antibiotic prophylaxis prior to ureteral stent removal "most of the time" by method of stent removal (stent on a string, office cystoscopy, or operating room (OR) cystoscopy) and surgery leading to stent placement (pyeloplasty, ureteroscopy, or ureteral reimplantation). Summary Figure